Co-composting of biodegradable municipal waste and fruit and vegetable wastes with indigenous microorganism for quality compost production - Musa, Aishatu Mala (2020)
Large quantity of organic waste generation from agricultural sectors and their disposal become a safety and health issues around the world. However, this material can be turn into useful products by composting process. Therefore. the objectives of the study were to produce a high-quality compost, measure its carbon and nitrogen mineralization, and evaluate the release of nutrient contents using maize as the test crop. The compost was prepared using horticultural- and biodegradable municipal-wastes with and without indigenous microorganisms (IMO). The nitrogen (N) contents of the composts ranged from 1.52 to 2.76% (equivalent to 76 to 138 kg N ha-1 at the rate of 5 Mg ha-1), while the other nutrients showed a significant variation due to the types of materials used. The initial C/N ratio declined in the range of 13.3 for 3:1+IMO compost to 26.0 for 1:2+IMO compost at the end of the 30 day of composting. Since initial separation was performed, the heavy metals were below permissible level by Malaysia standard MS1517 2012. Composts prepared at the ratio of 3:1 and 1:2 with and without IMO were superior in terms of plant nutrients content. In the soil incubation study, selected composts applied at the rate of 10 Mg ha-1 soil released the total-N (NH4 +- N and + NO3 --N) (in % over control) about 78.0 (3:1+IMO), 64.1 (1:2-IMO) and 64.4 % (1:2+IMO). At this rate, increased soil respiration rate was obtained for 3:1+IMO compost due to increased labile organic matter and higher amount of fruit and vegetable waste (FVW), which attract more soil microorganisms and/or the increased evolution of CO2 from compost-amended soils in the process of decomposition of the added composts. The DHA activity increased with composts application rates; and significantly highest for 3:1+IMO compost added at 10 Mg ha-1 soil at 1.38 triphenylformazan (TPF)/g dry soil/24 hours. A broad band between 3,200-3,600 cm-1 wavelength in the Fourier transform infrared (FTIR) spectroscopy indicates the presence of carboxylic and hydroxyl functional groups as a result of carbon transformation in the compost. The quality of compost was evaluated by growing of maize in the glasshouse using Munchong, Typic Paleudox soil series amended with composts 3:1-IMO, 3:1+IMO, 1:2 +IMO at 0, 5 and 10 Mg ha-1 application rates in polybags showed significant differences (P≤0.05) in plant biomass, plant aerial weight and nutrients uptake at 45 day after sowing (DAS) for N, P, K, Ca, and Mg. Total plant biomass measured ranged from 26.74 to 8.05 g plant-1 while the aerial portion ranged from 9.66 to 18.07 g plant-1. The means foliar nutrient concentrations at the application rate of 10 Mg ha-1 for compost 3:1 + IMO were 2.5 % N, 0.1 % P, 2.2 % K, 0.1 % Ca and 0.1% Mg. Composts using a 3:1 ratio with and without IMO at 10 Mg ha-1 application rate gave higher nutrient content and subsequently released more nutrients for plant uptake. Hence, both these composts are recommended to be used as soil amendments and organic fertilizers for plants.